Synthesis, Characterization and Structure of Copper(II) complex involving Chloride and Tridentae NNS coordinate Schiff base ligand (Communications in Inorganic Synthesis, 2017)
Mononuclear copper(II) complex [CuLCl2] where L = (2-methylsulfanyl-phenyl)-(phenyl-pyridin-2-yl-methylene)amine, a tridentate NNS donor Schiff base ligand has been synthesized and characterized by microanalysis, IR, UV-Visible spectra and magnetic studies. Crystal structure of the complex has been solved by single crystal X-ray diffraction studies and shows the complex has distorted trigonal bipyramidal geometry.